Non-magnetic spoof plasmonic isolator based on parametric amplification - Gao, Xinxin (2022)
Driven by the miniaturization of integrated electronics, research on spoof plasmonic circuits has recently aroused widespread interest. On the other hand, nonreciprocal devices, such as isolators and circulators, are key components of integrated electronic systems. However, bulky magnets required to realize isolation and circulation prevent the application of traditional nonreciprocal technologies to integrated systems. Here, parametric amplification is explored to achieve magnetic-free plasmonic isolation, and an ultrathin reconfigurable spoof plasmonic isolator is realized experimentally. In this isolation system, the forward signal amplified by a spoof plasmonic parametric amplifier is coupled to a second linear plasmonic waveguide via a spoof localized surface plasmon resonator, whereas the transmission from the inverse direction is prohibited, giving rise to a measured isolation ratio of up to 20 dB. By tuning the nonlinear phase-matching condition through external bias voltage, multi-frequency isolation of spoof surface plasmon polariton (SSPP) signals is also realized experimentally. This work demonstrates the possibility of producing miniaturized and low-cost non-reciprocal SSPP devices, holding great promise for applications in nonmagnetic information processing and radar detection.